(Curcumin+sildenafil) enhances the efficacy of 5FU and anti‐PD1 therapies in vivo. Issue 10 (27th January 2020) - Dent, Paul; Booth, Laurence; Roberts, Jane L.; Poklepovic, Andrew; Hancock, John F.
Abstract: We have extended our analyses of (curcumin+sildenafil) biology. The drug combination caused vascularization and degradation of mutant K‐RAS that correlated with reduced phosphorylation of ERK1/2, AKT T308, mTORC1, mTORC2, ULK1 S757, STAT3, STAT5, and NFκB and increased phosphorylation of eIF2α, ATM, AMPKα, ULK1 S317; all concomitant with elevated ATG13 S318 phosphorylation and autophagosome formation. Prior studies with drug combinations utilizing sildenafil have delineated an ATM‐AMPK‐ULK1 S317 pathway and an AKT‐mTOR‐ULK1 S757 pathway as modules which control ATG S318 phosphorylation and autophagosome formation. The knockdown of PKG reduced cell killing as well as reducing drug‐enhanced phosphorylation of ATM, AMPKα, and ATG13. In the absence of PKG, no significant increase in ULK1 S317 phosphorylation was observed. In a Beclin1‐dependent fashion, the drug combination reduced the expression of multiple histone deacetylase (HDAC) proteins, including HDAC2 and HDAC3. Molecular knockdown of HDAC2, HDAC3, and especially (HDAC2+HDAC3) significantly reduced the expression of PD‐L1 and elevated expression of Class I human major histocompatibility complex. In vivo, (curcumin+sildenafil) enhanced the efficacy of 5‐flurouracil against CT26 colorectal tumors. Prior exposure of established CT26 tumors to (curcumin+sildenafil) significantly enhanced the efficacy of a subsequently administered anti‐PD‐1 antibody. Collectively our data argue that (curcumin+sildenafil) has the potential in several settings to be an efficacious neoadjuvant therapy for colon cancer. Abstract : (curcumin+sildenafil) causes K‐RAS V12‐GFP and K‐RAS V12‐RFP to become located in intracellular vesicles.